DAMPAK SISTEM PENGELOLAAN AIR MINUM TERHADAP SOSIAL BUDAYA MASYARAKAT DI PULAU NUSA PENIDA - Nyoman Sudipa; Ketut Ariantana (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2023)
Nusa Penida is a dry island with low rainfall throughout the year reaching 1428.40 mm. Water is an important means of supporting community life and tourism in Nusa Penida. As the population grows, the need for water also increases, so water needs to be managed using a drinking water management system. The research uses a qualitative descriptive approach using social theory, namely Cultural Materialism Theory, to formulate the phenomenology of the socio-cultural impacts of drinking water system management on Nusa Penida Island. The research method uses a qualitative approach with primary data sources originating from direct observations of each phenomenon found and secondary data originating from interviews with relevant figures and experts. The aim of the research is to determine the impact of the drinking water management system on social culture on Nusa Penida Island. The research results show that the existence of resources on Nusa Penida Island is quite adequate, originating from underground water in Kutampi Kaler Village and the Penida, Guyangan and Seganing springs which are managed by PDAM Klungkung Regency. Water is a very expensive resource and affects the economic, social and cultural conditions of the Nusa Penida community. In the past, before the 2000s, most of the people in the upper classes spent part of their income to buy water, which caused the social conditions of the community to experience poverty, because during the dry season people would spend their time walking to coastal areas to fetch water. Cultural reduction in the form of religion also occurs by building communal communities as supporters of temples that have fresh water wells on the coast. It can be concluded that the drinking water management system on Nusa Penida Island has had an impact in the form of a shift in the social life of the Nusa Penida community, namely increasing community welfare due to economic substitution and changes in social patterns due to easy access to drinking water and the emergence of new business activities from the presence of drinking water as proven by the changes. The culture of the people of Nusa Penida is a shift from agricultural culture to industrial culture (tourism). Changes in community cultural patterns due to the availability of drinking water, namely a shift in community livelihood patterns from an agricultural basis to an industrial (tourism) pattern.